MIDCAB vs OPCAB for severe coronary artery disease: a comparative study. (25th November 2020) - Tartanus, J; Mueller, X; Syburra, T; Von Wattenwyl, R; Cuculi, F; Kobza, R; Matt, P
Abstract: Background/Introduction: MIDCAB (minimally invasive direct coronary artery bypass surgery) ± PCI/DES was compared to classical "off pump" coronary artery bypass surgery (OPCAB) for the treatment of severe coronary artery disease. Purpose: We hypothesized that MIDCAB is associated with reduced perioperative morbidity and mortality. Methods: Preoperative and postoperative clinical data were collected prospectively in 329 consecutive patients with severe coronary artery disease undergoing either a MIDCAB procedure ± PCI/DES (MIDCAB group), n=118 patients, or classical OPCAB (OPCAB group), n=211 patients, at our institution from January 2017 to July 2019. A matched analysis using the EuroSCORE II (81 patients per group) was done. Results: The median of EuroSCORE II was 1.05 in both groups, p=1. All MIDCAB patients underwent a left-sided mini-thoracotomy and received a single LIMA-LAD graft, OPCAB patients received median 3 distal anastomoses, p<0.001. Operative time was shorter in MIDCAB patients, 160min vs. 240min, p<0.001. Maximum postoperative Troponin levels were lower in MIDCAB compared to OPCAB, 105 μg/l vs. 260 μg/l, p<0.001. Intubation time was shorter in MIDCAB, 7.0 h vs. 9.3 h, p=0.04, as was ICU time, p=0.02. Chest tube drainage after 24 hours was lower in MIDCAB patients, 405 mL vs. 555 mL, p<0.001. Transfusions of blood, platelets and fresh frozen plasma were rarely needed. Transfusion of erythrocytes were more common in OPCAB, 19%, vs. MIDCAB, 2.5%, p=0.001. A transient neurological deficit showed one (1.2%) patient in the OPCAB group, non in MIDCAB, p=0.3. A hybrid procedure was performed in 18 MIDCAB patients (22%) and 5 OPCAB patients (6.2%). In-hospital mortality was 0% in the MIDCAB group, and 1.2% in OPCAB patients, p=0.3. Conclusions: MIDCAB is a good and safe option to treat severe coronary artery disease. MIDCAB is not only less invasive, but associated with reduced perioperative risk compared to standard OPCAB surgery even if a hybrid procedure is needed. Funding Acknowledgement: Type of funding source: None